Índice interno de esforço: uma proposta para a mensuração robusta de artefatos intelectuais desenvolvidos por servidores públicos - Oliveira, Alisson Antônio de (2024)
Within a scientific research project developed since 2014 at the Federal Institute of Paraná (IFPR) to create an automated feedback system for evaluating the intellectual work of federal public servants, it became necessary at a certain point to measure Explicit Intellectual Activities (EIA), such as books, scientific articles, software codes, patents, etc. Upon researching the subject, it was concluded that there was no generic method to help public servants robustly measure their work to generate effective results for the tax-paying society. The objective of this thesis is to demonstrate that by using solid philosophical premises, combined with good faith in the development of the work and robust mathematical structures, it is possible to create a system for measuring the material results created by the intellectual activities developed by public servants. The method created is characterized by being a sequential process to find the most appropriate variables for the automated and large-scale measurement of EIA, using correlation tests to minimize errors. The developed method was called the index of Internal Effort (IIE). In this thesis, the IIE was tested with five different datasets in the form of proofs of concept (PoC), and the results indicate that the IIE has a significant correlation with the specific techniques tested, thus presenting itself as a generic framework that can be used on a large scale in the measurement of EIA. During the PoC tests, no specific case was found that refuted the premise of using the IIE. However, it is noted in more than one section the importance of careful use and careful selection of variables to avoid biased measurements, whether due to the lack of expertise of the person responsible for the test or due to any corporatist action that may try to discredit the use of the method in evaluating the individual results in public service provided to society.